2017
DOI: 10.1016/j.stemcr.2017.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Surface Topography Guides Morphology and Spatial Patterning of Induced Pluripotent Stem Cell Colonies

Abstract: SummaryThe relevance of topographic cues for commitment of induced pluripotent stem cells (iPSCs) is largely unknown. In this study, we demonstrate that groove-ridge structures with a periodicity in the submicrometer range induce elongation of iPSC colonies, guide the orientation of apical actin fibers, and direct the polarity of cell division. Elongation of iPSC colonies impacts also on their intrinsic molecular patterning, which seems to be orchestrated from the rim of the colonies. BMP4-induced differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
106
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 57 publications
5
106
0
Order By: Relevance
“…Despite their uniform appearance, there is also marked heterogeneity within colonies of iPSCs [32,33]. Therefore, we analyzed if specific subclones become dominant during serial passaging of iPSCs.…”
Section: The Clonal Composition Of Ipscs Remains Relatively Stable Dumentioning
confidence: 99%
“…Despite their uniform appearance, there is also marked heterogeneity within colonies of iPSCs [32,33]. Therefore, we analyzed if specific subclones become dominant during serial passaging of iPSCs.…”
Section: The Clonal Composition Of Ipscs Remains Relatively Stable Dumentioning
confidence: 99%
“…Micropatterning tools have further uncovered the role of the cytoskeleton during differentiation through analysis of how RhoA/Rho-associated kinase (ROCK) impacts actomyosin contractility in MSCs undergoing fate decision toward adipocyte and osteocyte lineages (16)(17)(18)(19). Nonetheless, these studies rely on the presence of soluble cues, while studies exploring the undeveloped cytoskeletal structure of hiPSCs, as it relates to their differentiation capacity, have been relatively unexplored (20,21). Here we utilized micropatterning to show how the interplay between cytoskeletal tension (i.e., active forces developed by the cell) and local cell density, reported as the fraction of each local region occupied by nuclei, modulates mesodermal fate independently of soluble cues, which subsequently leads to vascular commitment from hiPSCs.…”
mentioning
confidence: 99%
“…Hereinafter, our results revealed that tested PLA macro‐topographies similarly influenced different DPSC orientation and morphology: wavy surface determined more straightened morphology of cells, meanwhile, DPSC seeded on porous scaffold were flatter and bent over on the PLA filament. Moreover, scaffold's macro‐topographies also influenced DPSC nuclei shape, although previously it was thought that only micro‐ and nano‐structures can influence cell morphology. Therefore, our results imply that surface pattern in the scale of >100 μm still alters cell shape and induces different ECM tensions which undoubtedly affect cell fate.…”
Section: Discussionmentioning
confidence: 62%